DEFORMATION OF WOOD IN COMPRESSION DURING MOISTURE MOVEMENT - S. Hamdan; M.S. Osman; M.Y. Chew (ASEAN Journal on Science and Technology for Development, 2008)
This work presents the phenomenon of mechano-sorptive strain in the deformation of wood during moisture content (MC) changes. A series of experiments were designed to demonstrate the greatly enhanced deformation due to the mechano-sorptive effect. The purpose of this work is to show the magnitude of mechano-sorptive creep compared to the ordinary viscoelastic creep with applied compressive load. In order to do this, several conditions were induced. They were the moisture movement with MC change, moisture movement without MC change and conditions without moisture movement. Several apparatus were assembled to produce the desired conditions. Special care is taken to make sure that the compressive load is relatively small and is within elastic limit. This work observed the unique patterns of strains of various conditions that were induced in the experiments. The characteristics shown in the results were evaluated logically and compared to existing theories to confirm their validity. The results have shown that with the presence of mechano-sorptive, the maximum strains of Jelutong (dyera costulata) wood specimens loaded at 200N is 0.433x10 -3 . The results showed that the severest deformation is caused by the increasing MC in the wood specimen, attributed to the mechanosorptive (MS) effect.